THE EFFECT OF MARGIN, SERVICE QUALITY AND COLLATERAL ON MURABAHAH FINANCING OF SMALL AND MEDIUM ENTERPRISES - Ubaydillah, Abdul Haris; Rahayu, Yayuk Sri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
Financial institutions provide financing services in order to meet the public's need for capital, especially for micro, small and medium enterprises. During the Covid-19 pandemic, murabahah contract financing was the most sought after by the public. Therefore, this study aims to determine the effect of margin, service quality, and collateral on murabahah financing. This study uses a quantitative type with a survey method. The population in this study is murabahah financing customers with a sample of 104 respondents. The research instrument test was carried out to test the validity and reliability. Data analysis used multiple linear regression analysis.The results showed that margin and service quality had a significant effect on murabahah financing. Meanwhile, collateral has no significant effect on murabahah financing. Based on the results of this study, financial institutions are expected to be able to provide information about murabahah margins transparently to customers so that they can increase the amount of murabahah financing. The collateral provided is more affordable for customers so that the application for murabahah financing can be comprehensive for small and medium entreprises.